FACTORS AFFECTING THE UPTAKE OF CERVICAL CANCER SCREENING SERVICES AMONG WOMEN AGED 15-49 YEARS ATTENDING KIBOGA HOSPITAL IN KIBOGA DISTRICT. A CROSS-SECTIONAL STUDY. - SSENTONGO, VICTOR; ANYWAR, LYDIA (Student’s Journal of Health Research Africa, 2024)
Background: The objectives are to find out the knowledge about cervical cancer screening services, sociodemographic factors affecting the uptake of cervical cancer screening services, and the attitude of women aged 15-49 years towards cervical cancer screening services attending Kiboga Hospital in Kiboga district. Methodology: The study employed the cross-sectional study design. This study was conducted at Kiboga Hospital in Kiboga District in the Outpatient Department from 5th July 2023 to 5th August 2023. Results: The results of the study were that the majority of the respondents, 55 (55%), did not know about cervical screening services, and 64% knew that cervical cancer screening should be done at least once. The majority, 58 (58%), said that cervical cancer screening was important because it ensures early diagnosis and treatment. The majority, 74 (74%) believed that cervical cancer screening is important. The majority, 62 (62%), believed that religious belief cannot protect them from cervical cancer. The majority of respondents, 57 (57%) aged 15-32 years were willing to participate in cervical cancer screening. The majority, 89 (89%) had never screened. Conclusion: The respondents had little knowledge about cervical cancer screening services and established that the sociodemographic factors affecting cervical cancer screening were the age of the respondent, employment, and level of education. It also found that the respondents had a good attitude towards cervical cancer screening. Recommendation: The Ministry of Health should do more health education for women about the existence of cervical cancer screening services, the government should ensure the empowerment of women in education and the government should empower women in employment through affirmative action. Also, the government should encourage women to cervical cancer screening. Health workers should continuously encourage women to participate in cervical cancer screening.